THE IMPACT OF TRANSFORMATIONAL LEADERSHIP, SELF- EFFICACY AND PROFESSIONAL COMPETENCE ON LECTURER PERFORMACE: EVIDENCE AT PRIVATE UNIVERSITY - Indra jaya; Citrawati Jatiningrum; Marilin Kristina (JURNAL EDUCATION AND DEVELOPMENT, 2024)
The performance of lecturers at private universities is very important in determining the progress and achievements of universities to become educational institutions that have the best reputation in society. This research aims to analyze the determining factors of lecturer performance at private universities. Several factors tested were transformational leadership, self-efficacy, and professional competence on lecturer performance. This study determined the sample using a purposive sampling technique from 8 private universities in Lampung Province. Using a quantitative approach and research data analysis techniques using Structural Equation Modeling (SEM) was completed through the Analysis Moment of Structural (AMOS) program. The research results show that there is an influence of transformational leadership, self-efficacy, and professional competence on the performance of private university lecturers. The transformational leadership factor has the strongest influence on the performance of public private university lecturers. Contribution of research findings to policy makers, especially private higher education leaders in implementing a leadership style in evaluating, supervising, providing encouragement for improving lecturer performance.